A preservação ambiental das propriedades camponesas na comunidade Serrinha em São José das Palmeiras - PR - Portz, Márcio Alexandre (2010)
The paper addresses the environmental preservation of the rural community Serrinha in São José das Palmeiras / PR. The preservation of the environment made by farmers is due to the peasant way of life based on environmental practices (soil conservation, water, agricultural practices, etc..), Limiting the use of natural resources, set at the discretion of subsistence family. Environmental protection is one of two ways: local issues related to the need for preservation of soil water, biodiversity linked directly with communities. And another one connecting the complex nature of the destruction of the local media in all regions of the world, for a change of natural processes such as ocean currents, global warming, evaporation of the seas, melting glaciers at the poles, etc. The evolution of the peasant way of life has important practical and productive organizations that develop into forms of production balanced with the environment. In the areas studied, these practices are presented in order to improve the condition of the natural elements of the property, also play a resistance of the peasants in their properties. The connection with political and social projects like the Cultivando Água Boar Program and Paraná Biodiversidade increases the financial conditions and the solutions of some environmental liabilities in small farms of the peasants. Peasants are a "class" vital to the continuation of the biodiversity of natural ecosystems; they are similar in their mode of finite life in their material needs.